Phase Control of Optical Nonreciprocity in Photonic Bandgap Four-Wave Mixing - Yunzhe Zhang; Irfan Ahmed; Dan Zhang; Zhe Liu; Weitao Zhang; Wenhui Yi; Yanpeng Zhang (IEEE Photonics Journal)
We investigate the optical nonreciprocity induced by the parametrical amplification and the radiation trapping in an atomic photonic bandgap system both theoretically and experimentally. We use two pumping fields to generate entangled photon pairs from spontaneous parametric four-wave mixing, as well as the signals in which they can be enhanced by the feedback dressing effect. Therefore, the frequency difference and the shape change due to this feedback dressing on the two-arm ramps of one round trip are observed. Such optical nonreciprocity can be easily controlled by multiple experimental parameters (frequency detuning, power, and phase) of the dressing beams. In addition, the enhancement and suppression switching induced by the double dressing or triple dressing conditions are also studied. This optical nonreciprocity can contribute to the development of quantum information processing and quantum communications.